Implementation of QFD Model (Quality Function Deployment) in Electronic Industries in Iran (Gilan Province) - Amirmostofian, Alireza (2010)
In the past, companies in electric industry like Pars Khazar in Gilan province did not follow Quality Function Deployment (QFD) model in their production processess. That was why they couldn\'t hear customers\' voices well; hence they did not allocate their sources appropriately along the customers needs in quality and design, resulting in lower rate of product selling and lower profit.